The Interplay Between Inflammation and Stromal Components in Pancreatic Cancer - Li, Ying; Wang, Jing; Wang, Haiyan; Zhang, Shaoqiang; Wei, Yingxin; Liu, Shanglong (Frontiers in Immunology, 2022)
Inflammation involves interactions between various immune cells, inflammatory cells, chemokines and cytokines in pancreatic cancer. Cancer cells as well as surrounding stromal and inflammatory cells establish an inflammatory tumor microenvironment (TME). Inflammation is closely associated with immunity. Meanwhile, immune cells are involved in both inflammation and immune response. Tumor-promoting inflammation and tumor-suppressive immunity are two main characteristics of the tumor microenvironment in pancreatic cancer. Yet, the mechanism of inflammation and immune response in pancreatic cancer development is still unclear due to the dual role of some cytokines and the complicated crosstalk between tumor and stromal components in TME. In this review, we outline the principal cytokines and stromal cells in the pancreatic TME that are involved in the tumor-promoting and immunosuppressive effects of inflammation, and discuss the interaction between inflammation and stromal components in pancreatic cancer progression. Moreover, the clinical approaches based on targeting TME in pancreatic cancer are also summarized. Defining the mechanisms of interplay between inflammation and stromal components will be essential for further development of anti-cancer therapies.